2014
DOI: 10.1371/journal.pone.0109181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peer Counselling by Mother Support Groups on Infant and Young Child Feeding Practices: The Lalitpur Experience

Abstract: ObjectiveOur primary objective was to evaluate the effect of peer counselling by mother support groups (MSG's) in improving the infant and young child feeding (IYCF) practices in the community.MethodsWe conducted this repeated-measure before and after study in the Lalitpur district of Uttar Pradesh, India between 2006 and 2011. We assessed the IYCF practices before and after creating MSG's within the community. The feeding practices were reassessed at two time points–2 (T1) and 5 years (T2) after the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 15 publications
5
63
0
Order By: Relevance
“…In a cluster-randomized controlled trial carried out in Bangladesh, the implementation of participatory women's groups led to significant increases in EBF for 6 months (15 %) and mean duration of breast-feeding (+38 d) in intervention v. control areas and pre-v. postintervention (92) . Similarly, in India, peer counselling through mother support groups showed improved initiation within an hour of birth, EBF and decreased prelacteal feeding at 2 and 5 years post-baseline (94) . The present review also underscores the importance of involvement of family members, who can influence when, what and how babies are fed (6,95) .…”
Section: Promising Interventions and Programmatic Implications Of Thementioning
confidence: 87%
“…In a cluster-randomized controlled trial carried out in Bangladesh, the implementation of participatory women's groups led to significant increases in EBF for 6 months (15 %) and mean duration of breast-feeding (+38 d) in intervention v. control areas and pre-v. postintervention (92) . Similarly, in India, peer counselling through mother support groups showed improved initiation within an hour of birth, EBF and decreased prelacteal feeding at 2 and 5 years post-baseline (94) . The present review also underscores the importance of involvement of family members, who can influence when, what and how babies are fed (6,95) .…”
Section: Promising Interventions and Programmatic Implications Of Thementioning
confidence: 87%
“…The study found that the intervention had a significant impact on the improvement of infant feeding practices. For instance, there was a significant improvement in the age-appropriate initiation of complementary feeding, 5 years after the intervention (96%) compared to 54% in pre-intervention period (OR 22.9, 95%CI:11.8–44.1, p  = < 0.001) [26]. However, a cluster-randomized controlled study conducted in Bangladesh that assessed the influence of a participatory womens’ group on infant feeding and other health outcomes in children did not find any differences in dietary diversity scores [27].…”
Section: Discussionmentioning
confidence: 99%
“…Counseling has been shown to be effective intervention to increase rates of early initiation of breastfeeding, reduce rates of prelacteal feeding and increase rates of exclusive breastfeeding. 5 At our centre we did not have dedicated breast-feeding counselors. Recently we started human milk banking at our centre and introduced lactation counselor first time in a phasic manner.…”
Section: Introductionmentioning
confidence: 99%